ENHANCINGOF PRACTICAL SKILLS ONTHE MAINTENANCE AND REPAIRING COMPETENCY OF AIR REFRIGERATIONVEHICLE FOR DROPOUT YOUTH - Rohendi, Dedi; Berman, Ega Taqwali; Suma, Enang; Sumardi, Kamin; Ariyano, Ariyano; Hardikusumah, Inu; Djohar, As’ari (Journal of Mechanical Engineering Education, 2020)
The government is trying to improve the ability of the community in entrepreneurship. This is done to overcome the increasing unemployment problem in the country. Expertise services are one of the factors that support entrepreneurship. One of the expertiseservices is filling and vacuuming the freon Air Conditioning of car. This expertise requires reliable human resources. However, until now the available resources are still limited. The training was conducted by lecturers from the Department of Mechanical Engineering UPI in line with the Tridharma Perguruan Tinggi activities on the skills of filling and vacuuming the freon AC of the car. The purpose of this training is to help out-of-school youths in Cigugur village, Kuningan regency who are not yet workingor in order to find work, so that they have basic skills in the car air-conditioning system so that they can be used for work or independent entrepreneurs. The methods used in this training are lectures, discussions, practice and improvement projects. Thetraining was conducted for 18 young people who dropped out of school in Cigugur village, Kuningan district. The results of the training show that there is a significant increase in the practical skills of maintaining and repairing air-conditioning youth cars that drop out significantly.